STATE SECURITY OF UKRAINE IN THE FACE OF MODERN CHALLENGES AND THREATS - Maltsev, Vitalii; Sharko, Denys; Dashkovskyi, Anatolii (Honor and Law, 2025)
The article emphasizes that modern challenges to national security are complex, multidimensional, and largely hybrid in nature. These challenges concern not only the military sphere, but also the information space, energy system, cyberspace, financial stability, political stability, and social cohesion of society. The study found that threats to Ukraine's national security are both external (military aggression, cybercrime, information warfare) and internal (corruption, political instability, weak institutions).Of particular importance is the effectiveness of the state's response mechanisms to challenges, its capacity for strategic planning, coordination of all security sectors, and interaction with international partners. Therefore, effective state security in Ukraine in the current environment requires: a systematic approach to identifying and neutralising threats; improvement of the regulatory and legal framework; strengthening the resilience of state institutions; introduction of modern technologies, particularly in the field of cyber defence; and enhancement of strategic communication and international cooperation.